Dragmaxia anomala sp.n. (Demospongiae: Halichondrida) from the southwestern Atlantic (Brazil) - Carvalho, Mariana De S.; Hajdu, Eduardo (Zootaxa, 2004)
A new species of Dragmaxia Hallmann, 1916 is described from the northern sector of the S o Paulo state coastline (Brazil), in the Tropical southwestern Atlantic. The new species, Dragmaxia anomala sp.n., differs from the other species of the genus, viz. D. variabilis (Whitelegge, 1907) and D. undata Alvarez et al., 1998, due to its raphides which are not acanthose.